2022
DOI: 10.1002/14651858.cd001704.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for improving mobility after hip fracture surgery in adults

Abstract: Analysis 5.4. Comparison 5 Quadriceps training programme versus conventional physiotherapy alone, Outcome 4Functional reach (inches).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 126 publications
1
33
0
Order By: Relevance
“…The strength of evidence for exercise in preventing falls in older adults after hip fracture is moderate [ 229 ]. This recommendation places a high value on preventing falls in this population with focus on mobility rehabilitation after hip fracture, including balance training and adequate pain control (see World Health Organisation guidelines).…”
Section: Specific Clinical Populationsmentioning
confidence: 99%
“…The strength of evidence for exercise in preventing falls in older adults after hip fracture is moderate [ 229 ]. This recommendation places a high value on preventing falls in this population with focus on mobility rehabilitation after hip fracture, including balance training and adequate pain control (see World Health Organisation guidelines).…”
Section: Specific Clinical Populationsmentioning
confidence: 99%
“…In general, the interventions focused on the recovery of mobility, especially in the acute phase, showed their effectiveness in improving walking speed, also through gait training [ 40 ] which was used by only 44% of the interviewees. Probably the reason why less than half of physiotherapists chose gait training is related to the still low prescription of full weight-bearing.…”
Section: Discussionmentioning
confidence: 99%
“…The Cochrane review of interest here analyzed the existing evidence on the effectiveness of interventions aimed to improve mobility after hip fracture surgery [3]. As an update to the previously published review from 2011 [5], the authors screened 3459 records and identified 21 new trials that met the eligibility criteria in addition to the previously included 19 trials on this topic.…”
Section: Importance Of the Topicmentioning
confidence: 99%